Identifying existing correlations between attention problems and non-adaptive behaviors in high school students - Călin, Mariana Floricica (Technium Social Sciences Journal, 2022)
Many teachers and students in high schools report numerous incidents of disruptive and inappropriate behavior. If these types of behaviors increase, a negatively correlated amount of time and effort of teachers can be consumed due to trying to manage a volatile environment in the classroom, generating a negative experience for both themselves and the students. First impressions matter. Starting from the first day of class, teachers should behave as leaders who are organized, prepared, able and prepared to take responsibility. This can mean allocating extra time to prepare for the first day of class to avoid feeling rushed or unbalanced. Managing the challenges of class policies discussed on day one in a respectful but firm tone will send the message that boundaries will be set constantly throughout the semester. It is much easier to establish strict guidelines, since exceptions arise, than to try to impose new limits once the class has already gotten out of control.